2020
DOI: 10.1016/j.brs.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stimulation of cervical vertebrae modulates the discharge activity of ventral tegmental area neurons and dopamine release in the nucleus accumbens

Abstract: Background: Growing evidence suggests that mechanical stimulation modulates substrates in the supraspinal central nervous system (CNS) outside the canonical somatosensory circuits. Objective/Methods: We evaluate mechanical stimulation applied to the cervical spine at the C7-T1 level (termed "MStim") on neurons and neurotransmitter release in the mesolimbic dopamine (DA) system, an area implicated in reward and motivation, utilizing electrophysiological, pharmacological, neurochemical and immunohistochemical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 42 publications
(46 reference statements)
1
27
0
Order By: Relevance
“…Further, we have demonstrated that mechanical activation of this neuronal pathway, though the dorsal column-medial lemniscus pathway, elicits the same responses. Additionally, these effects can be blocked by inactivation of nicotinic acetylcholine and delta-opioid receptors in the NAc, suggesting a role for cholinergic interneurons in the NAc [ 24 ]. Thus, we suggest that a long-lasting decrease in cocaine locomotion by HT7 acupuncture would be due to modulation of neurotransmitters such as β-endorphin, GABA, acetylcholine, and DA in VTA and NAc.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have demonstrated that mechanical activation of this neuronal pathway, though the dorsal column-medial lemniscus pathway, elicits the same responses. Additionally, these effects can be blocked by inactivation of nicotinic acetylcholine and delta-opioid receptors in the NAc, suggesting a role for cholinergic interneurons in the NAc [ 24 ]. Thus, we suggest that a long-lasting decrease in cocaine locomotion by HT7 acupuncture would be due to modulation of neurotransmitters such as β-endorphin, GABA, acetylcholine, and DA in VTA and NAc.…”
Section: Discussionmentioning
confidence: 99%
“…To date, pain relieving effects of vibration are most commonly attributed to the gate-control theory via the stimulation of somatosensory afferents; however, supraspinal mechanisms may be involved [60]. Recent studies have reported a decrease in gamma aminobutyric acid neuron firing activity [64] and an increase in dopamine neuron firing rates [65] in the ventral tegmental area of the brain in response to approximately 50 Hz. While these studies suggest vibration can modulate supraspinal central nervous system substrates, greater work is needed to better elucidate how they affect descending nociceptive influence.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence has suggested that the reward system links to external somatosensory system [24, 25]. Somatosensory stimuli such as noxious stimulation influence the activity of DAergic neurons in the reward system [24].…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory stimuli such as noxious stimulation influence the activity of DAergic neurons in the reward system [24]. Activation of cervical spine mechanoreceptors modulates firing of VTA GABA neurons and dopamine release [25]. Furthermore, we and others have shown that somatosensory stimuli reduce drug-induced craving behaviors through modulating the mesolimbic DA systems in rats [26, 27].…”
Section: Discussionmentioning
confidence: 99%